2016
DOI: 10.1542/peds.2015-3183
|View full text |Cite
|
Sign up to set email alerts
|

Work–Life Balance, Burnout, and Satisfaction of Early Career Pediatricians

Abstract: BACKGROUND AND OBJECTIVE: Data describing factors associated with work-life balance, burnout, and career and life satisfaction for early career pediatricians are limited. We sought to identify personal and work factors related to these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 29 publications
8
93
3
1
Order By: Relevance
“…Hematology as a discipline emerged in the late 19th and early 20th centuries with the advent of microscopy and practical methods to Over the past decade, there have been significant changes to the clinical practice of medicine, including but not limited to remarkable advances in our knowledge related to medicine, including PHO; growing PHO subspecialization; new care delivery models with increasing reliance on advanced practice providers (APPs) and hospitalists 2,3 ; broad implementation of electronic medical records in a variety of healthcare settings; specific emphasis on enhancing the quality of care delivery and patient safety; and the increasing value of work-life balance among younger generations of PHO providers. 4,5 The leadership of the American Society of Pediatric Hematology/Oncology (ASPHO), a professional organization whose mission includes advancing professional practice within PHO, recognizes these changes and the importance of having an accurate assessment of the current PHO practice and workforce. Some workforce data regarding general pediatrics and subspecialties have been published previously.…”
Section: Introductionmentioning
confidence: 99%
“…Hematology as a discipline emerged in the late 19th and early 20th centuries with the advent of microscopy and practical methods to Over the past decade, there have been significant changes to the clinical practice of medicine, including but not limited to remarkable advances in our knowledge related to medicine, including PHO; growing PHO subspecialization; new care delivery models with increasing reliance on advanced practice providers (APPs) and hospitalists 2,3 ; broad implementation of electronic medical records in a variety of healthcare settings; specific emphasis on enhancing the quality of care delivery and patient safety; and the increasing value of work-life balance among younger generations of PHO providers. 4,5 The leadership of the American Society of Pediatric Hematology/Oncology (ASPHO), a professional organization whose mission includes advancing professional practice within PHO, recognizes these changes and the importance of having an accurate assessment of the current PHO practice and workforce. Some workforce data regarding general pediatrics and subspecialties have been published previously.…”
Section: Introductionmentioning
confidence: 99%
“…Those having children reported significant level of economic satisfaction but personal un-satisfaction. However, a study on US pediatricians reported higher proportion of female pediatricians with children but this was not a factor in satisfaction [20]. Those earning more than their husbands reported significant higher economic as well as job satisfaction as they contributed more in their family and probably a higher status at workplace too.…”
Section: Discussionmentioning
confidence: 90%
“…Being notified well in advance also allows trainees to plan accommodation, employment for a partner and childcare 11. Knowledge of their work schedule more than 1 month in advance was found to be associated with increased satisfaction with life overall in one cohort study of early career paediatricians 12. Health Education England now mandates that trusts are notified of which trainees have been placed with them at least 3 months in advance 13.…”
Section: Configuration Of Specialty Training Programmesmentioning
confidence: 99%